2016
DOI: 10.18632/oncotarget.6969
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage targeting contributes to the inhibitory effects of embelin on colitis-associated cancer

Abstract: Macrophages are a major component of inflammatory and tumor microenvironment. We previously reported that embelin suppresses colitis-associated tumorigenesis. Here, the role of macrophage targeting in the anti-inflammatory and anti-tumor properties of embelin was investigated. By using colitis-associated cancer (CAC) model, we demonstrated that embelin significantly depleted colon macrophages by blocking their recruitment. Moreover, embelin attenuated M2-like polarization of macrophages within the tumor microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
(58 reference statements)
1
19
0
Order By: Relevance
“…In this context, it has been described that extended infiltration of neutrophils and production of ROS in cisplatin‐induced nephrotoxicity . In one reported literature, Wu et al has demonstrated inhibitory effects of embelin on colitis‐associated cancer through reducing an increased level of NF‐κB, TNF‐α, and IL1β . In another study, Meng et al have shown an anti‐inflammatory and antioxidant effect of embelin in myocardial infarction .…”
Section: Discussionsupporting
confidence: 85%
“…In this context, it has been described that extended infiltration of neutrophils and production of ROS in cisplatin‐induced nephrotoxicity . In one reported literature, Wu et al has demonstrated inhibitory effects of embelin on colitis‐associated cancer through reducing an increased level of NF‐κB, TNF‐α, and IL1β . In another study, Meng et al have shown an anti‐inflammatory and antioxidant effect of embelin in myocardial infarction .…”
Section: Discussionsupporting
confidence: 85%
“…It decreases the expression and production of pro-inflammatory cytokines and impairs the infiltration and function of tumor-associated macrophage (TAM) in the tumor milieu. 33 Our finding suggests that myeloid cells may be a critical target of embelin to achieve its therapeutic benefits in CAC.…”
Section: Introductionmentioning
confidence: 72%
“…We have previously reported that embelin not only resolved the colonic inflammation but also dramatically inhibited the colitis-associated tumor initiation and progression in an azoxymethane (AOM)/dextran sulfate sodium (DSS)induced CAC model. 32,33 Moreover, embelin treated mice exhibited a lower mortality rate than untreated controls during CAC challenge ( Figure 1A), suggesting that embelin significantly improves the long-term survival rate of tumorbearing mice. In addition, the spleen size of embelin-treated CAC-bearing mice was smaller than that of untreated group ( Figure 1B).…”
Section: Embelin Decreases Mdsc Accumulation In Spleen and Tumor In Cmentioning
confidence: 94%
See 1 more Smart Citation
“…*Also obtained from stokes of Caragana jubata ** Black currants, apples and cherries are also good sources of quercetin Aloe-emodin, a natural compound extract from Aloe Vera, has been discovered to suppress cell proliferation and accelerate apoptosis in a variety of tumor cells [514].…”
Section: Mundulea Sericeamentioning
confidence: 99%